Determinants of Farm Policies in the United States, 1996-2008 - Orden, David; Blandford, David; Josling, Timothy (World Bank, Washington, DC, 2017)
This paper focuses on the political economy of United States (U.S.) farm policy since the Uruguay round trade negotiations concluded in 1994 and established the World Trade Organization (WTO). The continued ability of the powerful farm lobby in the U.S. to elicit support in the political arena is evident from this analysis. Yet there have been some substantial changes in policy that have reduced their distortionary effects, as well as some setbacks to liberalizing reform. New Doha round commitments could put further constraints on subsidies provided by some U.S. policy instruments. And despite the ability of the farm lobby to retain its support programs through 2012, there are several political uncertainties about the alignments that have allowed U.S. farm support to endure.